2023
DOI: 10.3390/s23031547
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Inertial Sensors to Evaluate Gait Stability

Abstract: The portability of wearable inertial sensors makes them particularly suitable for measuring gait in real-world walking situations. However, it is unclear how well inertial sensors can measure and evaluate gait stability compared to traditional laboratory-based optical motion capture. This study investigated whether an inertial sensor-based motion-capture suit could accurately assess gait stability. Healthy adult participants were asked to walk normally, with eyes closed, with approximately twice their normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…When attaching the IMUs to these points using a cloth bandage, areas near joints where the attachment may loosen during extended periods of walking should be avoided. In practice, IMUs are typically affixed near the knee, either on the femoral or tibial parts [10,[51][52][53]. Considering these practical considerations for fixation, further research is needed to refine our understanding and approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When attaching the IMUs to these points using a cloth bandage, areas near joints where the attachment may loosen during extended periods of walking should be avoided. In practice, IMUs are typically affixed near the knee, either on the femoral or tibial parts [10,[51][52][53]. Considering these practical considerations for fixation, further research is needed to refine our understanding and approach.…”
Section: Discussionmentioning
confidence: 99%
“…A common objective of these indices is to facilitate the identification of such individuals, enabling the provision of appropriate interventions to mitigate fall risks [3]. In the pursuit of accessible measures for assessing fall risks, the potential of inertial measurement units (IMUs) for gait analysis has garnered significant interest [4][5][6][7][8][9][10]. For instance, Kim et al [4] employed an IMU sensor embedded in a shoe to calculate basic gait parameters such as stride and walking speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the equipment used in the data collection, IMU-based motion capture and instrumented insoles, are known to be less accurate than their traditional counterparts, optical motion capture and in-ground force plates 22 , 34 . One of our previous studies compared stability measures derived from the IMU suit and optical motion capture 38 . We found that although the accuracy of the IMU system may be reduced, they are still sensitive to changes in behaviour, allowing for meaningful insights to be gained.…”
Section: Discussionmentioning
confidence: 99%
“…We found no changes with the MoS and LDE stability measures, but it is possible that other stability measures might yield significant changes. Although wider step widths was the only significant stability-related change, inertial sensors cannot directly measure distance between each other, and estimates of step width may be less accurate than other spatiotemporal estimates [17,18,19]. In addition, the number of strides available for the LDE analysis was 109 strides, and more strides could lead to more precise estimates of λ s [20].…”
Section: Discussionmentioning
confidence: 99%